Tree Diversity, Species Composition, Forest Structure and Aboveground Biomass in Mixed Dipterocarp Forest, Bintulu, Sarawak - Malcom, Demies (Universiti Malaysia Sarawak, 2022)
Degradation and deforestation are occurring at a rapid pace in tropical forests, including those found in Sarawak. Thus, conservation of biodiversity, biomass, and carbon stocks can provide additional benefits to sustainable forest management in addition to sustainable timber production. Nonetheless, few studies have quantified their structure, biomass, and carbon content; critical information for a better understanding of tropical forests' global function. As a result, this study was conducted to (i) assess tree diversity and species composition, (ii) assess forest structure, (iii) estimate tree above-ground biomass (AGB), and (iv) estimate carbon storage in a mixed dipterocarp forest in the Anap Sustainable Development Unit (ASDU), Bintulu, Sarawak. A total of 61 plots covering a sampling area of 7.67 ha were established; 9 plots were located within the primary forest, while the remaining plots were located within the selectively logged area that was logged at various years. All trees with a diameter at breast height (Dbh) of at least 10 cm were identified, marked, and measured, as well as the composition, above-ground biomass, and carbon storage. A total of 5,893 stems were counted and identified, representing 73 families, 200 genera, and 794 species. The non-dipterocarp species dominated the tree population, accounting for 68.02 percent of all trees. The most dominant family is Dipterocarpaceae, while the most dominant genus is Shorea. Vatica micrantha is the most dominant species with a basal area of 7.42 m2 while Shorea parvifolia subsp. parvifolia has the highest Importance Values Index at 97.62%. The Shannon-Weiner diversity index (H') is high, ranging between 2.38 and 3.99, indicating a greater variety of tree species. This information is valuable in terms of establishing baseline data for the floristic composition and diversity of ASDU forests. The estimated average AGB for ASDU is 358.19 t ha-1, while the estimated average above-ground carbon stock is 168.35 t C ha-1. The AGB and carbon storage in the area were found to be highly dependent on the density of trees of various diameters, the age of the forest, and the diversity of tree species. Small trees with a Dbh of less than 50 cm accounted for 63.40 per cent of total AGB. A higher proportion of AGB in the smaller diameter classes indicates the critical role of small trees in carbon storage in natural forests. The study's findings indicate that ASDU forest has a high level of species diversity, AGB, and carbon storage. This was due to the presence of old secondary forests and remnants of primary forests within ASDU. However, logging activities and resource extraction left gaps in the forest structure that were colonised by non-dipterocarp. It shifted the species composition of trees of all sizes. Thus, in order to mitigate biodiversity loss, it is recommended that biodiversity surveys be integrated into the existing management system, as well as that sustainable logging practices be carefully planned and implemented.